Mutually Orthogonal Golay Complementary Sequences in Synthetic Aperture Imaging Systems - TROTS, Ihor (Archives of Acoustics, 2015)
The main objective of this study is to improve the ultrasound image by employing a new algorithm based on transducer array element beam pattern correction implemented in the synthetic transmit aperture (STA) method combined with emission of mutually orthogonal complementary Golay sequences. Orthogonal Golay sequences can be transmitted and received by different transducer elements simultaneously, thereby decreasing the time of image reconstruction, which plays an important role in medical diagnostic imaging.The paper presents the preliminary results of computer simulation of the synthetic aperture method combined with the orthogonal Golay sequences in a linear transducer array. The transmission of long waveforms characterized by a particular autocorrelation function allows to increase the total energy of the transmitted signal without increasing the peak pressure. It can also improve the signal-to-noise ratio and increase the visualization depth maintaining the ultrasound image resolution.In the work, the 128-element linear transducer array with a 0.3 mm pitch excited by 8-bits Golay coded sequences as well as one cycle at nominal frequencies of 4 MHz were used. The comparison of 2D ultrasound images of the phantoms is presented to demonstrate the benefits of a coded transmission. The image reconstruction was performed using the synthetic STA algorithm with transmit and receive signals correction based on a single element directivity function.